Wnt5a is strongly expressed at the leading edge in non-melanoma skin cancer, forming active gradients, while canonical Wnt signalling is repressed. - Celine Pourreyron; Louise Reilly; Charlotte Proby; Andrey Panteleyev; Colin Fleming; Kathleen McLean; Andrew P South; John Foerster (PLoS ONE)
Wnt5a is one of the so-called non-canonical Wnt ligands which do not act through β-catenin. In normal development, Wnt5a is secreted and directs the migration of target cells along concentration gradients. The effect of Wnt5a on target cells is regulated by many factors, including the expression level of inhibitors and receptors. Dysregulated Wnt5a signalling facilitates invasion of multiple tumor types into adjacent tissue. However, the expression and distribution of Wnt5a in cutaneous squamous cell carcinoma (SCC) and basal cell carcinoma (BCC), as well as the effect of Wnt5a on keratinocyte migration has not been studied in detail to date. We here report that Wnt5a is upregulated in SCC and BCC and localised to the leading edge of tumors, as well as tumor-associated fibroblasts. The Wnt5a-triggered bundling of its receptor Fzd3 provides evidence of Wnt5a concentration gradients projecting into the tumor. In vitro migration assays show that Wnt5a concentration gradients determine its effect on keratinoctye migration: While chemotactic migration is inhibited by Wnt5a present in homogenous concentrations, it is enhanced in the presence of a Wnt5a gradient. Expression profiling of the Wnt pathway shows that the upregulation of Wnt5a in SCC is coupled to repression of canonical Wnt signalling. This is confirmed by immunohistochemistry showing lack of nuclear β-catenin, as well as absent accumulation of Axin2. Since both types of Wnt signalling act mutually antogonistically at multiple levels, the concurrent repression of canonical Wnt signalling suggests hyper-active Wnt5a signal transduction. Significantly, this combination of gene dysregulation is not observed in the benign hyperproliferative inflammatory skin disease psoriasis. Collectively, our data strongly suggest that Wnt5a signalling contributes to tissue invasion by non-melanoma skin cancer.